IMAGE-SCANNING APPROACH IN MONITORING OIL PALM ROOT PRODUCTION ON PEAT - Elisa, Rumpang; Nik Sasha Khatrina, Khairuddin; Tiara Nales, Nyawai; IZZATI, MOHAMAD NOOR; NUR MAISARAH, JANTAN; LAW, MEI CHING; Sim, Siong Fong (Malaysian Palm Oil Board, 2026)
Understanding root mortality and production is critical for creating a uniform strategy for root growth estimations and modelling. Several approaches have been devised to assess root development and behaviour of oil palms in peat soil. There are two types of existing techniques: Traditional (destructive) methods and non-destructive approaches. However, due to the complexity of soil characteristics and circumstances, there is no precise method to date for assessing different root morphological features, particularly in tropical peat soil. The root dynamics performance of oil palms in peat soil was measured using a non-destructive, in situ scanning approach in this study. This study discusses the possibility of utilising image-scanning technology for investigating rhizosphere activities such as root development and turnover, root morphology and belowground interactions.